Performance and Operating Costs Oil Palm Fronds Chopper Machine Designed by Agricultural Mechanization Unit of North Sumatra Province - Handyman M. Waruwu; Lukman Adlin Harahap; Achwil Putra Munir (Jurnal Rekayasa Pangan dan Pertanian, 2016)
Chopping is one way of size reduction of solids into smaller pieces to produce solids of a certain size. Chopping with a mechanical equipment has not much been done due to lack of knowledge and limitation of existing equipment of the farmers. In fact, if it can be done can increase farmers' income. The aim of the research was to test the performance of oil palm fronds chopper machine designed by Agricultural Mechanization Unit in North Sumatra Province using oil palm fronds as a raw material and analyze its operating costs. Observed parameters were effective capacity, yield of chopping, the percentage of materials left behind, and fuel consumption of the equipment. The results showed that the effective capacity of the equipment was 287,29Kg/hour. Chopping yield was 94,2%. The percentage of materials left behind was 5,2%. Fuel consumption was 0,44 L/hour. Cost of Analysis was Rp. 53,9/Kg for the first year, Rp. 54,29/Kg for the second year, Rp. 54,48/Kg for the third year, Rp.54,79/Kg for the fourth year, and Rp. 55,12/Kg for the fifth year. BEP was 62.209 Kg in the first year, 65.862 Kg in the second year, 67.759 Kg in the third year, 70.755 Kg in the fourth year and 73.947 Kg in the fifth year. The IRR was 39,17%. Key words: chopper machine, oil palm fronds, operating costs, performance